Terapi Musik untuk Menurunkan Stres dan Meningkatkan Subjective Well-Being pada Dewasa Awal yang Memiliki Riwayat Perceraian Orang Tua - Akta Ririn Aristawati; Tatik Meiyuntariningsih; Ananda Putri (Philanthropy: Journal of Psychology)
Abstract: The increase in divorce cases that occur in Indonesia from year to year has caused many victims, one of them is children. The majority of children who have a history of parental divorce can have high stress and low subjective well-being. One form of effective treatment is music therapy. This study uses an experimental quantitative approach with a pretest-posttest control group design. The subjects in this study were divided into two groups consisting of 5 subjects in the experimental group and 5 subjects in the control group. Data were obtained through two scales, namely the stress scale and the subjective well-being scale. This study used an independent sample t-test with p value = 0.028 (p < 0.05) for stress and p = 0.008 (p < 0.05) for subjective well-being. These results indicate that there are significant differences in the control and experimental groups. Thus, it can be concluded that music therapy is effective for reducing stress and increasing subjective well-being significantly in early adults who have a history of parental divorce. Keywords: Adults, Broken Home, Music Therapy, Stress, Subjective Well-Being